Countering Fraud Committed Using Information Technology in Kazakhstan - TEMIRZHANOVA, Lyazzat А.; IMANGALIEV, Nurtai K.; SAGYMBEKOV, Bakhytzhan Zh.; ESHNAZAROV, Almaz A.; SYZDYKOV, Almaz Zh. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).25, 2019)
The relevance of this article is that with the development of modern technologies, conditions have formed for the emergence of such a new type of crime as fraud committed with the help of modern information technologies. Today in Kazakhstan, the amount of damage caused and the number of facts of this type of crime in recent years has grown many times. The practice of law enforcement indicates that computer technology is increasingly acting as a tool for committing crimes. Most of these crimes can cause real harm to a person and the state. The aim of the article is to study the theoretical and practical aspects of countering a new type of fraud. The methodological base of the article is composed of general scientific principles, approaches and methods of scientific knowledge, dialectical and comparative methods of cognition of social and legal processes and phenomena. The theoretical and practical significance of the article lies in the fact that the results of the work can become the foundation for amendments to the legislation of Kazakhstan, as well as for the development of methodological manuals on the investigation of the type of criminal offenses in law enforcement.